IDENTIFIKASI KOMPETENSI GURU SEBAGAI CERMINAN PROFESIONALISME TENAGA PENDIDIK DI KABUPATEN SUMEDANG (KAJIAN PADA KOMPETENSI PEDAGOGIK) - Suhandani, Deni; Julia, Julia (Universitas Pendidikan Indonesia, 2014)
This paper examines one of the main teachers' competence, ie pedagogical competence of teachers who have been certified educators in Sumedang district. This type of research is a survey research with descriptive-quantitative method. The population was 592 certified teachers in the district of North and South Sumedang, with a sample of 60 teachers. Data collected through questionnaire (Likert scale) on the respondent one (R1) is a certified teacher of 60 people, two respondents (R2) are colleagues who have not been certified 60 people, and three respondents (R3) is the principal of 60 people, so total respondents amounted to 180 people. Processing and data analysis was performed using SPSS 16 through frequency analysis and correlation. The results stated that the average pedagogical competence of teachers at the GOOD category, with the acquisition value of 3.02 (75.48%). However, when seen by the results of the correlation answer, where answer between R1 and R2 are many significant / agree, but the answers are not many significant R3 / contrary, it can be concluded that the average pedagogical abilities certified teacher educators in Sumedang district, is in the category ENOUGH based on answers from 150 respondents (84.3%), and is in the category GOOD based on answers from 28 respondents (15.7%). Keywords: pedagogical competence, professionalism, teacher, sumedang.